Isolation and Antioxidant and Antibacterial Activity of Flavonoid from Ficus variegate Blume - Rolan Rusli; Bela Apriliana Ningsih; Agung Rahmadani; Lizma Febrina; Vina Maulidya; Jaka Fadraersada (Indonesian Journal of Chemistry, 2019)
Ficus variegata Blume is specific plant of east Kalimantan. Flavonoid compound of Ficus variegata Blume was isolated by vacuum liquid and column chromatography, with previously extracted by maceration method using n-hexane and methanol, and fractination using ethyl acetate solvent. Eluent used in isolation were n-hexane:ethyl acetate (8:2). The results of elucidation structure by using spectroscopy methods (GC-MS, NMR, and FTIR) was obtained 5-Hidroxy-2-(4-methoxy-phenyl)-8,8-dymethyl-8H-pyrano[2,3-f] chromen-4-one. This compound has an antibacterial and antioxidant activities.